Longitudinal Association Between Orthostatic Hypotension at 30 Seconds Post-Standing and Late-Life Depression. - Kennelly, Sean; Kenny, Rose; Briggs, Robert (My University, 2018)
There is an established cross-sectional association between orthostatic hypotension (OH) and late-life depression. The aim of this observational study was to clarify the longitudinal association between baseline symptomatic OH (sOH-30) and incident depression in a sample of >3000 older people without baseline depression (mean age: 62 years at baseline). This study was embedded within the Irish Longitudinal Study on Ageing using data from waves 1 to 3, collected between 2009 and 2014. At 2- and 4-year follow-up, a score ≥9 on the 8-item Center for Epidemiological Studies Depression Scale was used to define incident depression. sOH-30 was defined as a drop in systolic blood pressure ≥20 mm Hg or diastolic blood pressure ≥10 mm Hg at 30 seconds post-standing in conjunction with orthostatic symptoms, such as dizziness, using beat-to-beat measurements. Almost one fifth (proportion, 18%; 95% confidence interval [CI], 16–20) of the study sample had sOH-30. One tenth (proportion, 10%; 95% CI, 9–12) had incident depression. Participants with incident depression were twice as likely to have sOH-30 at baseline compared with those without incident depression (linear regression, 13% [95% CI, 8–19] versus 7% [95% CI, 6–8]). Weighted logistic regression models demonstrated that sOH-30 predicted incident depression with an odds ratio of 1.90 (95% CI, 1.15–3.15) after controlling for covariates, including subthreshold depression, hypotension, cognitive impairment, and antidepressant use. Asymptomatic OH at 30 seconds and initial OH did not predict depression. This study demonstrates that sOH-30 predicts incident depression in a population-representative sample of older people and may, therefore, represent a potentially modifiable risk factor for late-life depression.
PUBLISHED
Keywords: Blood pressure; Depression; Dizziness; Hypotension, orthostatic; Risk factors; Ageing